2004
DOI: 10.1097/01.alc.0000125349.99823.8a
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Channel Analyses of Ethanol Modulation of Neuronal Nicotinic Acetylcholine Receptors

Abstract: These changes in single-channel parameters indicate that ethanol stabilizes the alpha4beta2 receptor-channel in the opening state, explaining how the maximum acetylcholine-induced whole-cell currents are further potentiated by ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
(62 reference statements)
6
14
0
Order By: Relevance
“…Our findings pertaining to α4β2-nAChR that are consistent with other reports of the existence of two conductance states (Buisson and Bertrand, 2001, Curtis et al, 2002, Nelson et al, 2003, Zuo et al, 2004). Zuo et al found conductance values very similar to those described here (Zuo et al , 2004); however, many other studies described various conductance states of α4β2-nAChR different from our findings here.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings pertaining to α4β2-nAChR that are consistent with other reports of the existence of two conductance states (Buisson and Bertrand, 2001, Curtis et al, 2002, Nelson et al, 2003, Zuo et al, 2004). Zuo et al found conductance values very similar to those described here (Zuo et al , 2004); however, many other studies described various conductance states of α4β2-nAChR different from our findings here.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings pertaining to α4β2-nAChR that are consistent with other reports of the existence of two conductance states (Buisson and Bertrand, 2001, Curtis et al, 2002, Nelson et al, 2003, Zuo et al, 2004). Zuo et al found conductance values very similar to those described here (Zuo et al , 2004); however, many other studies described various conductance states of α4β2-nAChR different from our findings here. One conductance of 20 pS was described for the chick α4β2 nAChR (Ballivet et al, 1988, Cooper et al, 1991), whereas two different conductances (15 and 34 pS) were observed for the rat α4β2 nAChR (Papke et al , 1989) and Pereira et al reported two conductance states (18 and 30 pS) from chick α4β2 nAChR (Pereira et al , 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Ethanol enhanced ACh-elicited inward currents for several nAChR subtypes expressed in Xenopus oocytes, including α4β2 nAChRs (Cardoso et al, 1999). Single channel recordings from cells expressing cloned α4β2 nAChRs indicates that ethanol enhances ACh-induced currents by stabilizing the open state of the receptor (Zuo et al, 2004). ACh, presumably released from mesopontine axon terminals, is present in VTA slices and contributes to baseline α6* nAChR activity in VTA DA neurons (Drenan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This action of ACh at mPFC layer VI pyramidal neurons contributes to the critical role of prefrontal cholinergic signaling to support optimal attention performance in situations requiring high attentional demand (Dalley et al, 2004; Parikh et al, 2007; Bailey et al, 2010; Howe et al, 2010; Guillem et al, 2011). Acute ethanol exposure increases ACh efficacy at α4β2* nAChRs (Aistrup et al, 1999; Cardoso et al, 1999; Zuo et al, 2004), whereas chronic ethanol exposure decreases α4β2* nAChR content (Robles and Sabriá, 2008; Hillmer et al, 2014) and may also decrease nAChR function in vivo (Majchrzak and Dilsaver, 1992). Chronic ethanol exposure during rat development impairs memory and attention in adulthood (Reyes et al, 1989; Nagahara and Handa, 1997; Woolfrey et al, 2005; Brys et al, 2014) and decreases the beneficial effects of nAChR stimulation to augment these mPFC-dependent functions (Nagahara and Handa, 1999).…”
Section: Introductionmentioning
confidence: 99%